APLIKASI PENJADWALAN PIKET HARI LIBUR BAGI KARYAWAN PT. ASTRA INTERNASIONAL.Tbk (AUT0 2000) PALEMBANG - Acep Juliandri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
From the results of research conducted on the data or information obtained about the needs that are needed, it will become the employee scheduling application program. To do data processing, employee scheduling at PT. Astra Internasional, Tbk ( Auto2000) Palembang which provides sales, maintenance, repair and supply of Toyota spare parts that are still being done using Excel Office Microsoft. How to make a schedule that takes a long time? To overcome these problems, it is necessary to have a new computerized system to improve work efficiency by making PT. Astra Internasional, Tbk ( Auto2000) Palembang Employee Picking Application Schedule. This system produces, Employee Pickup Schedule using PHP and MySQ.